PENEGAKAN HUKUM ATAS TINDAK PIDANA PENGGUNAAN BAHAN PELEDAK (BOM IKAN) DALAM PENANGKAPAN IKAN DI WILAYAH PERAIRAN LAUT INDONESIA - Alvi Kaban, Muhammad; Harahap, M.Syahnan (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
Indonesian regulations have an extraordinary spirit in eradicating fishing with explosives (fish bombs) by creating Law 31 of 2004 in conjunction with Law 45 of 2009 concerning Fisheries. Therefore, it is very interesting and important to further study how to regulate the criminal act of using explosives (fish bombs) in fishing in Indonesian sea waters? And the law enforcement of the criminal act of using explosives (fish bombs) in fishing in Indonesian sea waters? To answer this problem, a normative juridical legal research method was used with a statutory and conceptual approach method. Data obtained from primary, secondary, and tertiary legal sources were collected and then analyzed using qualitative data analysis techniques. From the results of the study, it was found that the regulation of the criminal act of using explosives (fish bombs) in fishing in Indonesian sea waters is regulated in Article 8 of Law 31 of 2004 in conjunction with Law 45 of 2009. Violation of the provisions of Article 8 is a criminal act as regulated in Article 84 of Law 31 of 2004 in conjunction with Law 45 of 2009. Meanwhile, law enforcement for criminal acts of using explosives (fish bombs) in fishing in Indonesian waters is carried out through preventive and repressive efforts. Preventive efforts made by the government are as follows: 1) Legal counseling; 2) Water Patrol; 3) Development of Marine Surveillance Facilities. The repressive efforts made in law enforcement for criminal acts of using explosives (fish bombs) are in the form of action in the waters; investigation and prosecution of perpetrators of criminal acts of using explosives (fish bombs).